Ideological pluralism in Kazakhstan: The state language in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
Main issues of developing state language of Kazakhstan, development of the state-forming nation, liberal views on ethnic relations in some states, comparative analysis of development of the state language in some countries and the ways of legal permits, the ideology of the language in our country are considered in the articleKey words: formation of national consciousness, a state ideology, now online values, assimilation of people, national diasporas, outlook, integration role.